Shaping Speechlessness after February 24, 2022 in the Magazine "ROAR" - Jakub Kapičiak (Studi Slavistici)
This study analyzes essays published in the magazine “Resistance and Oppositional Art Review” (“ROAR”), which was established after the full-scale Russian invasion of Ukraine. The study focuses on the motif of speechlessness that appeared in many texts by authors contributing to the magazine during the first month after February 24, 2022. The inquiry shows that the motif may acquire different forms and relate to various emotions such as guilt, shame, and fear. The author of this study argues that the motif is used not only as a specific emotional response to ongoing events but also as a medium to communicate a political statement of disagreement with the Russian invasion. Thus, it is possible to consider the magazine roar and its contributors as an emotional community